2014
DOI: 10.1007/978-3-319-09698-8_6
|View full text |Cite
|
Sign up to set email alerts
|

On Two Algorithmic Problems about Synchronizing Automata

Abstract: Under the assumption P = N P, we prove that two natural problems from the theory of synchronizing automata cannot be solved in polynomial time. The first problem is to decide whether a given reachable partial automaton is synchronizing. The second one is, given an n-state binary complete synchronizing automaton, to compute its reset threshold within performance ratio less than d ln (n) for a specific constant d > 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…Namely, checking whether a given strongly connected PFA is exactly synchronizing can be done in polynomial time, and for strongly connected exactly synchronizing PFAs with n states, there exits a cubic in n upper bound on the minimum length of exactly synchronizing words-both these facts readily follow from a result in [32]. However, Berlinkov [3] has shown that in the absence of strong connectivity, testing a given PFA for exact synchronization becomes PSPACE-complete; he has also constructed is a series of n-state PFAs whose shortest exactly synchronizing words have length of magnitude 2 Ω(n) . Thus, for the general case, problems related to exact synchronization are no less complicated than those related to careful synchronization.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Namely, checking whether a given strongly connected PFA is exactly synchronizing can be done in polynomial time, and for strongly connected exactly synchronizing PFAs with n states, there exits a cubic in n upper bound on the minimum length of exactly synchronizing words-both these facts readily follow from a result in [32]. However, Berlinkov [3] has shown that in the absence of strong connectivity, testing a given PFA for exact synchronization becomes PSPACE-complete; he has also constructed is a series of n-state PFAs whose shortest exactly synchronizing words have length of magnitude 2 Ω(n) . Thus, for the general case, problems related to exact synchronization are no less complicated than those related to careful synchronization.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Later, Gerbush and Heeringa [11] used the log n−approximation hardness of SetCover [9] to prove that O(log n)-approximation of the shortest reset word is NP-hard. Finally, Berlinkov [7] extended their result to hold even for the binary alphabet, and conjectured that a polynomial time O(log n)-approximation algorithm exists. We refute the conjecture by showing that, for every constant ε > 0, no polynomial time n 1−ε −approximation is possible unless P = NP.…”
Section: Previous Work and Our Resultsmentioning
confidence: 95%
“…Our construction will use Σ = {0, 1, 2}, which can be then reduced to the binary alphabet using the method of Berlinkov [7]. It is based on encoding every letter in binary and adding some intermediate states.…”
Section: Alphabet Sizementioning
confidence: 99%
See 2 more Smart Citations